2012
DOI: 10.5055/ajdm.2012.0093
|View full text |Cite
|
Sign up to set email alerts
|

High-fidelity multiactor emergency preparedness training for patient care providers

Abstract: Background: Providing comprehensive emergency preparedness training (EPT) for patient care providers is important to the future success of emergency preparedness operations in the United States. Disasters are rare, complex events involving many patients and environmental factors that are difficult to reproduce in a training environment. Few EPT programs possess both competency-driven goals and metrics to measure life-saving performance during a multiactor simulated disaster.Methods: The development of an EPT c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 61 publications
(40 reference statements)
0
15
0
Order By: Relevance
“…These publications include preliminary cognitive and self-assessment data as well as limited small group and mass-casualty-incident (MCI) skill assessment data. [16][17][18]…”
Section: Curriculum Developmentmentioning
confidence: 99%
“…These publications include preliminary cognitive and self-assessment data as well as limited small group and mass-casualty-incident (MCI) skill assessment data. [16][17][18]…”
Section: Curriculum Developmentmentioning
confidence: 99%
“…[6][7][8][9] Following brief didactic and small group sessions, interprofessional teams of four to six trainees were observed in a large university-based simulator designed to recreate environmentally challenging, multi-patient scenarios using high-fidelity human simulators and professional patient actors. A curriculum task force established nine learning objectives, 18 competencies, and 34 performance objectives.…”
Section: Novel Curriculum Developmentmentioning
confidence: 99%
“…Simulation as a modality has been a core means for training and evaluating performance of health care workers involved in a disaster response. [4][5][6][7] Some evidence has demonstrated that simulation offers a superior and longer-lasting learning experience than traditional didactic methods alone when training medical staff to manage and treat pediatric disaster victims. 8 The experiential learning activity focusing on disaster management must construct a realistic incident in which providers care for multiple injured patients while simultaneously coping with numerous stressors designed to tax an institution's resources.…”
Section: Introductionmentioning
confidence: 99%